Employee Performance Improvement at the Grand Mercure Hotel Jakarta Kemayoran Through Talent Development Initiatives - Al Agus Kristiadi; Raja Ulamin Debataraja; Parlagutan Silitonga (International Journal of Science and Society, 2022)
To propose a model increasing employees' work performance in Hotel Grand Mercure Kemayoran, Jakarta. This research method is quantitative. They are collecting data with instruments that have been tested for validity and reliability by sending a google form and using the accidental sampling technique, which is a sampling technique based on the chance for each element or member of the population to be selected as a sample (Sugiyono, 2013). A total of 100 samples were successfully collected, the data was processed by SEM using SmartPLS 3.2.9. Discipline and competence affect Talent Development Initiatives. Punishment does not affect Performance; indirect effect Discipline through the mediating role of Talent Development Initiatives on Performance has no effect. Competence affects performance either directly or indirectly through the mediation of the Talent Development Initiative. From the managerial aspect, continuously improve competence, skills, and knowledge as well as work attitude by speeding up the work followed by an awareness of work discipline on time, and obeying the rules according to SOPs, as well as planned work rotations to motivate employees to improve the quality of employee performance. according to the target that has been set.